Thoracolumbar fractures: Factors predicting failure of percutaneous short- and long-segment posterior fixation - David Ferreira; António Cruz; Ana Vilela; Joana Azevedo; André Santos Moreira; João Pereira; Paulo Gil Ribeiro; Nuno Oliveira; Pedro Varanda; Bruno Direito-Santos (Brain and Spine)
Introduction: Thoracolumbar (TL) transition trauma is frequent and challenging. Although short- (SSPF) and long-segment posterior fixation (LSPF) are its mainstay treatment, little is known about their failure rates and reasons behind it. Research question: understand why TL instrumentations fail and what factors influence it. Materials and methods: Retrospective, cohort, unicentric analysis on adult patients with acute TL trauma treated with percutaneous transpedicular SSPF or LSPF. Two groups were created, according to the presence of treatment failure at follow-up. We analyzed whether age ≥65 years old, fracture segment, posterior ligamentous complex (PLC) injury, load sharing classification (LSC) score >6, type of instrumentation (SSPF vs LSPF) and abnormal bone mineral density (BMD) were associated with failure. To achieve this, we evaluated radiological parameters at the preoperative, postoperative and follow-up appointments. Results: 87 patients were included: 60 (69.0%) without failure and 27 (31.0%) with. Age ≥65 years old (aOR = 3.66, p = 0.020), PLC injury (aOR = 2.94, p = 0.048) and SSPF (aOR = 6.75, p = 0.013) were statistically significant factors contributing to failure. The first two also presented shorter times to failure (35.2 vs 69.1 months, p = 0.013, and 25.2 vs 69.1 months, p = 0.037, respectively). In PLC injured patients, there was no statistically significant difference between SSPF vs LSPF. Discussion and conclusions: We conclude that age >65 years old, PLC injury and SSPF may be correlated with instrumentation failure. The first two factors were also associated with a shorter time to failure.